BDS: boycott, divestment, sanctions : the global struggle for Palestinian rights - Barghouti, Omar (2011)
Why now? -- Why BDS? -- The South Africa strategy for Palestine -- Academic boycott : moral responsibility and the struggle against colonial oppression -- Just intellectuals? Oppression, resistance, and the public role of intellectuals -- Freedom versus "academic freedom" : debating the British academic boycott -- Reflecting on the cultural boycott -- Fighting apartheid in South Africa, celebrating apartheid in Israel : open letter to Nadine Gordimer -- Between South Africa and Israel : UNESCO's double standards -- What we really need! A response to anti-boycott arguments -- Derailing injustice : Palestinian civil resistance to the "Jerusalem light rail" -- "Boycotts work" : Omar Barghouti interviewed by Ali Mustafa -- Boycotting Israeli settlement products : tactic versus strategy -- Our South Africa moment has arrived -- After the freedom flotilla atrocity : BDS takes off -- Leadership, reference, and the role of Israeli anticolonialists : Omar Barghouti interviewed by Maxine Kaufman-Lacusta